ALPHA-ADRENERGIC PATHWAYS IN THE LATERAL HYPOTHALAMUS ARE IMPORTANT FOR THE DIPSOGENIC EFFECT OF CARBACHOL INJECTED INTO THE MEDIAL SEPTAL AREA - Callera, J. C.; Saad, W. A.; Camargo, LAA; Menani, José Vanderlei [UNESP]; Renzi, Antonio [UNESP]; Abraosaad, W. (Associação Brasileira de Divulgação Científica (ABRADIC), 1995)
We studied the effect of the alpha(1)- and alpha(2)-adrenergic receptors of the lateral hypothalamus (LH) on the control of water intake induced by injection of carbachol into the medial septal area (MSA) of adult male Holtzman rats (250-300 g) implanted with chronic stainless steel cannulae into the LH and MSA. The volume of injection was always 1 mu l and was injected over a period of 30-60 s. For control, 0.15 M NaCl was used. Clonidine (20 nmol) but not phenylephrine (160 nmol) injected into the LH inhibited water intake induced by injection of carbachol (2 nmol) into the MSA, from 5.4 +/- 1.2 ml/h to 0.3 +/- 0.1 and 3.0 +/- 0.9 ml/h, respectively (N = 26). When we injected yohimbine (80 nmol) + clonidine (20 nmol) and prazosin (40 nmol) + clonidine (20 nmol) into theLH, water intake induced by injection of carbachol into the MSA was inhibited from 5.4 +/- 1.2 ml/h to 0.8 +/- 0.5 and 0.3 +/- 0.2 ml/h, respectively (N = 19). Water intake induced by carbachol (2 nmol) injected into the MSA was decreased by previous injection of yohimbine (80 nmol) + phenylephrine (160 nmol) and prazosin (40 nmol) + phenylephrine (l60 nmol) from 5.4 +/- 1.2 ml/h to 1.0 +/- 0.7 and 1.8 +/- 0.8 ml/h, respectively (N = 16). The cannula reached both the medial septal area in its medial portion and the lateral hypothalamus. It has been suggested that the different pathways for induction of drinking converge on a final common pathway. Thus, adrenergic stimulation of alpha(2),-adrenoceptors ofLH can influence this final common pathway.
Keywords: LATERAL HYPOTHALAMUS; SEPTAL AREA; A(1)- AND A(2)-ADRENOCEPTORS; CHOLINERGIC RECEPTORS; WATER INTAKE